Extração, caracterização e confirmação das estruturas dos ácidos graxos majoritários presentes no óleo da terminalia catappa linn (castanhola) através de técnicas espectroscópicas - Lima, Antonio Jefferson dos Passos (2016)
Terminalia catappa linn also known as castanets is belonging to the family of combretaceae and is found throughout the Brazilian coast. Although it is not a native species, it has ease germination and high resistance to salinity that lead it to become invasive. The fruits of castanets collected around UFPB campus showed almonds rich in oil with yield around 26% obtained by mechanical extraction. The triacylglycerides in the oil have showed a direct influence in the physical and chemical properties as acid value, iodine, peroxide, specific gravity and viscosity rheological factor. The results of these analyzes proved that the samples were in good condition of conservation. Furthermore, the results obtained from analytical thermogravimetry technics showed good thermooxidative stability to decomposition of the samples. The gas chromatography analysis coupled with mass spectrometer suggested that the palmitate, elaidate, linoleate and stearate as major methyl esters constituents of the triacylglycerides responsible for the evaluated properties.These esters were confirmed by the most important spectroscopic techniques to discuss structural elucidation of organic molecules such as FTIR, 1H and 13C NMR, COSY and HSQC.